Towards the EU Capital Market: The Impact of the ‘FASTER’ Directive - Teixeira, Glória; Santos, Tatiana (Journal of Finance and Financial Law, 2025)
The purpose of the article. This article aims to analyse the ‘FASTER’ Directive and to examine the relevance of its measures, as well as the possible consequences of their implementation. Methodology. Reports from the European institutions, specifically from the European Parliament, the proposal for a Council Directive and the Directive 2025/50 were consulted. National and international literature on the subject was also analysed in order to better understand the doctrine’s perspectives on the subject. Results of the research. This study revealed that the adoption of a Directive is the best solution for resolving the issues of double taxation and complicated and costly procedures for refunding of withholding tax. This will enable a joint response to the phenomena of tax fraud and abuse, which have caused Member States to lose huge amounts of revenue. The introduction of the new measures will enable an increase in cross-border investment, benefiting the single market and preventing the cases of cum-cum and cum-ex.